Spatial planning in the future: Requirements, topics and tasks from the point of view of planning practices - Priebs, Axel; Gnest, Holger (Raumforschung und Raumordnung | Spatial Research and Planning, 2008)
In a world of change, regional planning in Germany has permanently to deal with new demands and challenges. Against this background, the article analyses the tasks of spatial planning, regarding their future significance for planning practice. As shown, “products” and key issues of planning remain of great importance while there is a need for customised strategies for different types of regions. Furthermore, requirements for planners are given to increase the political and public perception of spatial planning
Keywords: Regionalplanung; Raumordnung; Zukunft; Raumtypen; strategische Planung